Reconstruction of Pretibial Defect Using Pedicled Perforator Flaps - Shin, In Soo (The Korean Society of Plastic and Reconstructive Surgeons, 2012)
BACKGROUND: Coverage of defects of the pretibial area remains a challenge for surgeons. The difficulty comes from the limited mobility and availability of the overlying skin and soft tissue. We applied variable pedicled perforator flaps to overcome the disadvantages of local flaps and free flaps on the pretibial area. METHODS: Eight patients who had the defects in the anterior tibial area were enrolled. Retrospective data were obtained on patient demographics, cause, defect location, defect size, flap dimension, originating artery, pedicle length, pedicle rotation, complication, and postoperative result. The raw surface created following the flap elevation was covered with a split thickness skin graft. RESULTS: Posterior tibial artery-based perforator flaps were used in five cases and peroneal artery-based perforator flaps in three cases. The mean age was 54.3 and the mean period of follow-up was 6 months. The average size of the flaps was 63.8 cm(2), with a range of 18 to 135 cm(2). There were no major complications. No patients had any newly developed functional deficit of the lower leg. CONCLUSIONS: We suggest that pedicled perforator flaps can be an alternative treatment modality for covering pretibial defects as a simple, safe and versatile procedure.